(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2025)
Due to the ramifications of the COVID-19 pandemic, several university students may find themselves unable to engage in conventional English language learning in a physical classroom setting. The imposition of online English instruction compromised the efficacy and outcomes of students’ English learning. Therefore, there is a need for a diverse range of technology, media, and platforms to enhance their educational achievements. Using mobile devices and wireless networks to interact with other devices may improve the effectiveness of online English learning for students. To investigate university students’ learning behaviors and attitudes, when using e-learning to study English, the current study aimed to assess curiosity, self-efficacy, equipment, experience, perceived ease of use, perceived utility, attitude towards using e-learning resources for English language acquisition, and the actual use of those technologies. This study used questionnaires sent to 4 universities, resulting in a total of 751 valid surveys. This research used Smart-PLS 4.0 to analyze the structural model and validate the hypotheses. The hypothesis testing findings revealed that attitude is the most influential factor in determining the adoption of e-learning for English language acquisition. Both results indicate that variables in the TAM (ease of use and usefulness) have a significant impact on e-learning use outcomes. Likewise, interest, self-efficacy, equipment, and experience factors are influencing e-learning use. In this regard, the research outcome provides rich theoretical understanding and immense practical explanatory power in language acquisition